1993
DOI: 10.1677/jme.0.0100313
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and cardiac paracrine actions of insulin-like growth factor-I (IGF-I) during thyroid dysfunction in the rat: is IGF-I implicated in the mechanism of heart weight/body weight change during abnormal thyroid function?

Abstract: Thyroid hormones are essential for the normal growth and development of many tissues. In the rat, hypothyroidism is associated with growth impairment, and hyperthyroidism with the development of a hypercatabolic state and skeletal muscle wasting but, paradoxically, cardiac hypertrophy. The mechanism by which thyroid hormone produces cardiac hypertrophy and myosin isoenzyme changes remains unclear. The role of IGF-I, an anabolic hormone with both paracrine and endocrine actions, in producing cardiac hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Although hypothyroidism lowers circulating and liver IGF-I concentrations, hyperthyroidism does not seem to modify serum or hepatic levels of this hormone in male or non-pregnant rats (7,49,50). We also observed no significant modifications in liver mRNA concentration of IGF-I in virgin rats or during pregnancy, but the postpartum increase was advanced, perhaps reflecting the advancement in luteolysis and parturition (3).…”
Section: Discussionmentioning
confidence: 45%
“…Although hypothyroidism lowers circulating and liver IGF-I concentrations, hyperthyroidism does not seem to modify serum or hepatic levels of this hormone in male or non-pregnant rats (7,49,50). We also observed no significant modifications in liver mRNA concentration of IGF-I in virgin rats or during pregnancy, but the postpartum increase was advanced, perhaps reflecting the advancement in luteolysis and parturition (3).…”
Section: Discussionmentioning
confidence: 45%
“…Methimazoleinduced hypothyroidism decreased circulating IGF-I levels in broilers (Decuypere et al 1987). Thomas et al (1993) reported similar serum IGF-I concentrations, but a 70% reduction in serum IGF-I bioactivity and reduced body weight in hyperthyroid rats compared with control animals. If such a reduction in bioactivity occurred in the present study, a reduction in skeletal muscle protein synthesis would be conceivable, despite no significant alteration in circulating, immunoassayable IGF-I concentrations.…”
Section: Gh-thyroid Axis Interactions: Consequences For Muscle Growthmentioning
confidence: 86%
“…Ojamaa et al (1992) demonstrated that thyroid hormone upregulated the expression of the myosin heavy chain genes. Thomas et al (1993) showed that insulin-like growth factor-I produced cardiac hypertrophy, as well as endocrine and cardiac paracrine effects, during hyperthyroidism. Based on these previous literature reports, it seems likely that the animal model of hyperthyroidism-induced cardiac hypertrophy is in fact multi-factorial in its mechanistic nature.…”
Section: Discussionmentioning
confidence: 99%